Biomass power plant prospects in Indonesia’s energy transition: IPP and PLN perspectives - Indra A. Aditya; Hendry Timotiyas Paradongan; Iswan Prahastono; Sudjono Kosasih; Kevin M. Banjar-Nahor; Ngapuli Irmea Sinisuka (Heliyon)
In an attempt to accelerate the energy transition, the government of Indonesia released a new regulation regarding renewable energy tariffs, including for biomass power plants (BPPs). However, a gap persists in the academic literature focusing on biomass power plants under these new tariffs. This study examines the role of biomass power plants (BPP) in meeting Indonesia's renewable energy targets, with a specific focus on recently introduced renewable energy tariffs. Three scenarios were developed to comprehensively understand Indonesia's state-owned electricity company (PLN) perspective and Independent Power Producers (IPPs) perspective, with a case study in Kundur Island, Riau Province. The financial analysis for IPPs shows in an NPV of $1.8 million under the initial tariff, while the expansion tariff results in an NPV of -$0.3 million. Sensitivity analysis reveals that a capacity factor exceeding 94.5 % is required to yield a positive NPV under the expansion tariff. From PLN's perspective, BPPs under the initial tariff correspond to an NPV of $8.48 million, and a B-C ratio of 2.31, resulting in a financially viable project, due to substantial cost savings from de-dieselization. Furthermore, the emission analysis highlights an 83.7 % decrease in emissions emitted with the utilization of BPPs compared to diesel power plants. These findings underscore the need to incorporate average generation cost in formulating renewable energy tariffs. Ensuring renewable energy projects are economically sustainable for both PLN and IPPs, stimulates widespread adoption and sustains cost-savings, all while advancing energy transition and making energy more accessible for everyone.